Improving Compliance With Food Safety Legislation. - Griffith, Chris (British Food Journal., 2005)
The BRG also welcomed a number of guests who spent time working with the Group on their own projects. The focus has been primarily on biomedical research and clinical medicine, although some work has been done in other areas. The new methods allow subject-based analysis to take place in ways that have not previously been possible and have led to many reports for clients and publications in journals. Previously published in: International Marketing Review, Volume: 107, Number 3, 2005.